The Use of Hedging Devices in Literature Review Sections of Undergraduate Thesis - Suaib Suaib (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
This study is to explore the use of hedging device in undergraduate studens thesis, focussed on literature review section. The objective of this study are: 1). To find out the typical features of formal class of hedging device employed by undergraduate students in literature review sections of their thesis, 2). To find out the typical features of informal/less-formal class of hedging device employed by undergraduate students in literature review sections of their thesis. The significance of the research is intended to help both teachers and students in developing the skills of academic writing discourse. Especially for the students and researchers, it expected by this research it would improve their awareness to employ approppriate words or vocabularies in asserting the claims of their future research findings. Due to the qualitative design of this study the instrument applied was document, while the sample theses were taken purposively. The gathered data of 10 literature review sections of undergraduate thesis written on 2015 by the students of Muhammadiyah University of Makassar analyzed and classified using Hinkels’ Classification of Hedges. The research findings revealed that Indefinite modal verbs ‘should’, ‘may’, and ‘able’ as the typical features of formal class of hedging device, meanwhile the definite modal verbs ‘can’, ‘will’ and ‘must’ were the typical feature of informal/less-formal class hedging device.